Evaluation of the effectiveness of sepiolite, bentonite, and phosphate amendments on the stabilization remediation of cadmium-contaminated soils. (15th January 2016) - Sun, Yuebing; Sun, Guohong; Xu, Yingming; Liu, Weitao; Liang, Xuefeng; Wang, Lin
Abstract: A pot trial was conducted to assess the effectiveness of sepiolite, bentonite, and phosphate on the immobilization remediation of cadmium (Cd)-contaminated soils using a set of variables, namely, physiological traits, sequential extraction procedure, plant growth and Cd concentration, and soil enzymatic activities and microbial population. Results showed that superoxide dismutase and peroxidase activities in the leaves of Oryza sativa L. and catalase activities in soils were stimulated after applying the amendments. However, soluble protein contents in leaves and urease and invertase activities in soils were reduced from 7.1% to 31.7%, 1.0%–23.3%, and 21.1%–62.5%, respectively, compared with the control. Results of the sequence extraction procedures revealed that the exchangeable fraction of Cd in soils was mostly converted into carbonated-associated forms. The water soluble plus exchangeable fraction (SE) of Cd in soil decreased when treated with single and compound materials of sepiolite, bentonite and phosphate, which resulted in 13.2%–69.2% reduction compared with that of CK (control test). The amendments led to decreased Cd concentrations in roots, stems, leaves, brown rice, and rice hull by 16.2%–54.5%, 16.6%–42.8%, 19.6%–59.6%, 5.0%–68.2%, and 6.2%–20.4%, respectively. Higher bacterial and actinomycete amount indicated that remediation measures improved soil environmental quality. Composite amendments could be more efficiently used for the stabilization remediation of Cd contaminated soils with low Cd uptake and translocation in the plants and available contents of Cd in soil. Highlights: The effect of sepiolite, bentonite and phosphate on Cd immobilisation is studied. The amendments are effective in immobilizing Cd in soils. The remediation measures improve soil quality.